The potential of the synergistic use of passive and active remote sensing measurements for the validation of a regional dust model - Amiridis, Vassilis; Kafatos, Menas; Pérez García-Pando, Carlos; Kazadzis, S.; Gerasopoulos, Evangelos; Mamouri, Rodanthi-Elisavet; Papayannis, Alexandros D.; Kokkalis, Panagiotis; Giannakaki, Elina; Basart, Sara; Daglis, Ioannis A.; Zerefos, Christos S. (My University, 2009)
A long-lasting Saharan dust event affected Europe on 18-23 May 2008. Dust was present in the free troposphere over Greece, in height ranges between the surface and approximately 4-5 km above sea level. The event was monitored by ground-based CIMEL sunphotometric and multi-wavelength combined backscatter/Raman lidar measurements over Athens, Greece. The dust event had the maximum of its intensity on 20 May. Three-dimensional dust spatial distribution over Greece on that day is presented through satellite synergy of passive and active remote sensing using MODIS and CALIPSO data, respectively. For the period under study, the ground-based measurements are used to characterize the dust event and evaluate the latest version of the BSC Dust Regional Atmospheric Modeling (BSC-DREAM) system. Comparisons of modeled and measured aerosol optical depths over Athens show that the Saharan dust outbreak is fairly well captured by BSC-DREAM simulations. Evaluation of BSC-DREAM using Raman lidar measurements on 20 May shows that the model consistently reproduces the dust vertical distribution over Athens.
Keywords: Aerosols; Remote sensing; Optical radar; Troposphere